Inequities in neurology amplified by the COVID-19 pandemic - Nolen, LaShyra (Nat Rev Neurol, 2021)
This year, the COVID-19 pandemic has altered neurological care in many ways. However, evidence indicates that people from marginalized ethnic and socioeconomic groups have been affected by these changes more than others, highlighting and amplifying existing health-care disparities.